Movements of the “poors of christ” in the middle ages: Saint Francis and Saint Domingue - Álvarez Calderón, Jorge (2014)
The work reflects on the main theme of poverty in the framework of the origin and fast growth of Franciscans and Dominicans, who since 1220, without having made contact with each other, in the span of only seventy years, had a profound influence on the renewal process of the Church of the thirteenth century. Although the two founders had no relationship at the beginning, and being so different in their intuitions, history connects and acknowledges them as initiators of the called “mendicant orders” and therefore, as an expression of generational claim to an authentic ecclesial reform in the sense of a return to the sources, and in particular, to Christ and the poor. Both, perhaps without measuring how insightful and timely they were, collected central spiritual concerns of his time and correctly canalized them for the good of the whole Church. The reception among their contemporaries is sufficient indication that their proposal responded yesterday-and today- to a heartfelt need.